MERAWAT ALAM SEBAGAI IBADAH: EKOTEOLOGI ISLAM DAN ETIKA LINGKUNGAN DI PONDOK PESANTREN DARUSSALAM PUNCAK BANYUWANGI - Nur Hafifah; Ahmad Syamsul Muarif; Indifatul Anikoh (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
The environmental crisis in agrarian regions of Banyuwangi challenges the role of Islamic boarding schools (pesantren) as agents of ecological transformation through Islamic ecotheology. This study examines how environmental stewardship is understood and practiced as an act of worship at Pondok Pesantren Darussalam Puncak, focusing on theological constructions (tawḥīd khilāfah), everyday environmental ethics, and the integration of ecological practices into religious life. The primary objective is to reveal the relational nexus between humans, nature, and God within the ecological habitus of santri through an interpretive qualitative case study. The research employed in-depth interviews with ten informants (kiai, santri, and administrators) and systematic observation over a two-month period. Data were analyzed using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing/verification. The findings identify three central themes: a theological framing of nature as a divine trust (amānah), ritualized practices such as collective communal work (ro’an) understood as acts of worship, and institutional constraints, particularly limitations in ecological infrastructure. The study concludes that Islamic ecotheology at Pesantren Darussalam shapes environmental ethics through the mediation of kiai authority and the ritualization of ecological habitus, although these processes remain constrained by structural limitations. The theoretical contribution of this study lies in proposing a contextual model of “practical ecotheology” rooted in East Javanese pesantren culture. Practically, the findings suggest the integration of ḥifẓ al-bi’ah (environmental preservation) as a compulsory curriculum component to support the national replication of green pesantren initiatives.